The “Metonymic Return Ticket” of Proper Names: A Cognitive Analysis of Anthroponymic Idioms - Muhitdinov Dilshod Tokhirovich (International Journal of Literature and Language Studies, 2026)
Abstract: Traditional structuralist approaches have long treated idioms as non-compositional, frozen lexical units, while classical onomastics often views proper names as rigid designators devoid of semantic intension. This article challenges both paradigms by investigating the semantic fluidity of anthroponymic idioms (e.g., not know someone from Adam, a Doubting Thomas, raise Cain) through the lens of cognitive linguistics.